Diffusion of ICT and SME Performance : the mediating effects of integration and utilisation - Azam, Md Shah (Curtin University, 2014)
This research examines the diffusion of ICT and its impact on SME performance with a special focus to the mediating effects of integration and utilisation of ICT. Applying a mixed method research approach, a qualitative field study followed by a quantitative survey, the study revealed that ICT usage didn’t contribute firm performance immediately. However Integration and proper utilisation are important variables which mediate the impact of ICT use on firm performance.